2012
DOI: 10.1016/j.worlddev.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Identity, Inequality, and Happiness: Evidence from Urban China

Abstract: This paper presents the impact of income inequality on the subjective wellbeing of three different social groups in urban China. We classify urban social groups according to their hukou status: rural migrants, "born" urban residents, and "acquired" urban residents who had changed their hukou identity from rural to urban. We focus on how the income disparity between migrants and urban residents affects individual happiness. The main results are as follows. People feel unhappy if inequality is related to their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
106
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 29 publications
(21 reference statements)
19
106
2
2
Order By: Relevance
“…Most of our findings are consistent with previous studies in China: education and income are positively associated with SWB (Appleton and Song 2008;Chen and Davey 2008a;Knight et al 2009;Knight and Gunatilaka 2010a); being divorced or unemployed has a negative association with SWB (Jiang et al 2012;Shu and Zhu 2008); health status is positively associated with SWB (Appleton and Song 2008;Chyi and Mao 2011;Knight et al 2009;Monk-Turner and Turner 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Most of our findings are consistent with previous studies in China: education and income are positively associated with SWB (Appleton and Song 2008;Chen and Davey 2008a;Knight et al 2009;Knight and Gunatilaka 2010a); being divorced or unemployed has a negative association with SWB (Jiang et al 2012;Shu and Zhu 2008); health status is positively associated with SWB (Appleton and Song 2008;Chyi and Mao 2011;Knight et al 2009;Monk-Turner and Turner 2011).…”
Section: Discussionsupporting
confidence: 92%
“…After controlling for region and socio-economic characteristics SWB decreased with age until the age group 55-64 years and was then approximately constant. Other studies have found a U-shaped relationship between age and SWB, with the lowest SWB between 30 to 50 years, depending on the study settings (Appleton and Song 2008;Jiang et al 2012;Knight and Gunatilaka 2010a;Monk-Turner and Turner 2011). However, after controlling for also subjective health status (SRH or VAS), SWB was relatively constant with age, with a tendency for a somewhat lower SWB in the middleaged age groups and a U-shaped age pattern, which is similar to previous findings in China (Appleton and Song 2008;Knight et al 2009;Knight and Gunatilaka 2010a).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…While China has exhibited high economic growth, it has also experienced rising income inequality (Xie and Zhou 2014). Yet another set of studies have examined the effect of rising income inequality in China on wellbeing (Jiang et al 2012;Wang et al 2015).…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…One of the features of China's growth experience has been the household registration (hukou) system, which has restricted the rights of rural-urban migrants in Chinese cities. Several studies have examined various aspects of hukou status for the wellbeing of rural-urban migrants (Afridi et al 2015;Cheng et al 2014a;Jiang et al 2012;Zhang and Treiman 2013).…”
Section: Introduction and Overviewmentioning
confidence: 99%